Psycho-physiological symptoms of stress and fatigue in elite male fencers during one-day tournament. A pilot study - Obminski, Z.; Mroczkowska, H.; Zdanowicz, R.; Kownacka, I.; Blach, W. (Journal of Combat Sports and Martial Arts, 2014)
This study was undertaken in order to revealed the hormonal, metabolic and perceived fatigue among male fencers taking part in a one-day fencing tournament. Material and methods. Five elite Polish fencers of an international skill level took part in European Fencing Championships. The competition started in the forenoon (10:00 am, eliminatory hits) and ended in the evening (c.a.18:00 pm, final fights) and these two rounds were separated by 2-hour intermission. During the entire tournament each contestants played 7-9 fights and majority of them were won. In capillary blood samples taken four times during the event, pre/post the eliminations and finals, serum cortisol (C ) and testosterone (T) and lactate levels were determined. Directly after each sampling state anxiety (SA), mood state (MS) and physical well-being (PW-B). Results. Based on the final outcome each examined subject was successful. During the whole competition SA and MS scores were unchanged and indicated on a positive psychological status. After the last fight PW-B was markedly decreased, the level of C was the highest, of T and T:C ratio were the lowest, and PW-B showed physical fatigue. CK was significantly elevated next day. Conclusions. Fencing competition elicited disadvantage shift in the hormonal status indicating high rate of catabolism and induces increased perceived physical fatigue in elite male contestants. Mood state and anxiety state are unchanged over the event, likely due to the successes achieved in the subsequent fights.